2021
DOI: 10.20944/preprints202112.0270.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Characterization of Circulating DENV-2 During Outbreak in Northern Senegal, Rosso 2018

Abstract: Globally 390 millions of people are at risk of dengue infection; over the past 50 years the virus incidence increased thirty-fold. In Senegal, an unprecedented occurrence of outbreaks and sporadic cases was noticed since 2017. In October 2018 an outbreak of DENV-2 was reported in Rosso area in the north of Senegal at the border with Mauritania. Out of the 187 blood specimen samples collected, 27 were positives by qRT-PCR and 8 were serologically positive for DENV IgM. Serotyping using qRT-PCR reveals that isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…21 According to data from WHOCC for arboviruses and hemorrhagic fever viruses, DENV-2 is continuously circulating in Senegal since 2014 (unpublished data); interestingly during all reported outbreaks since 2017, DENV-2 was identified as the dominant serotype only during epidemics in Rosso in 2018 (Northern Senegal). 32 Knowing that determinants of DENV fitness, pathogenesis, and disease outcome are multifactorial, our present study results revealed the circulation of DENV-2 strains belonging to two different clades of DENV-2 cosmopolitan genotype in Senegal in 2018. Previous studies revealed that many parameters linked to virus epidemiology as interserotypic immune reactions, the epidemic cycle of serotypes, genotype, or clade replacement can be affected by the incidence and the co-circulation of different DENV serotypes.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…21 According to data from WHOCC for arboviruses and hemorrhagic fever viruses, DENV-2 is continuously circulating in Senegal since 2014 (unpublished data); interestingly during all reported outbreaks since 2017, DENV-2 was identified as the dominant serotype only during epidemics in Rosso in 2018 (Northern Senegal). 32 Knowing that determinants of DENV fitness, pathogenesis, and disease outcome are multifactorial, our present study results revealed the circulation of DENV-2 strains belonging to two different clades of DENV-2 cosmopolitan genotype in Senegal in 2018. Previous studies revealed that many parameters linked to virus epidemiology as interserotypic immune reactions, the epidemic cycle of serotypes, genotype, or clade replacement can be affected by the incidence and the co-circulation of different DENV serotypes.…”
Section: Discussionmentioning
confidence: 54%
“…Since 2017 to date recurrent dengue outbreaks with co‐circulation of many serotypes (DENV‐1‐3) are reported in Senegal 21 . According to data from WHOCC for arboviruses and hemorrhagic fever viruses, DENV‐2 is continuously circulating in Senegal since 2014 (unpublished data); interestingly during all reported outbreaks since 2017, DENV‐2 was identified as the dominant serotype only during epidemics in Rosso in 2018 (Northern Senegal) 32 . Knowing that determinants of DENV fitness, pathogenesis, and disease outcome are multifactorial, our present study results revealed the circulation of DENV‐2 strains belonging to two different clades of DENV‐2 cosmopolitan genotype in Senegal in 2018.…”
Section: Discussionmentioning
confidence: 99%
“…This system has allowed for the notification of many DENV outbreaks in Senegal [ 12 , 13 , 16 ]. Despite the recurrence of dengue epidemics, case studies focusing on the circulating serotypes/genotypes and their associated spatial and temporal distribution are limited [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first urban dengue epidemic took place in 2009 and was caused by DENV-3. This was followed by yearly outbreaks affecting different regions of the country [ 12 , 13 , 14 ] and linked to different serotypes [ 12 , 15 , 16 ]. Despite the recurrent reports, few studies have assessed the virus diversity in Senegal [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive Viral Research Panel (CVRP) was used to obtain the viral whole genome. The RNA extract was reverse transcribed with the SuperScript IV Reverse Transcriptase kit (Invitrogen, Thermo Fisher, USA), and cDNA was fragmented before a telomere repair, a dA-Tailing, a ligation step with Universal Twist adapters before a final libraries amplification as previously described (6). A single pooled library was prepared from the indexed samples, and hybridized targets were bound to streptavidin beads.…”
Section: A Target Enrichment Standard Hybridization Workflow Using Tw...mentioning
confidence: 99%